Endovascular treatment of posterior communicating artery aneurysms in the presence of the fetal variant of posterior cerebral artery - Chen, Zhi (Interv Neuroradiol, 2015)
Posterior communicating artery (PcomA) aneurysms in the presence of the fetal variant of posterior cerebral artery (PCA) often pose technical challenges for endovascular treatment because of a greater potential for ischemic injury with the fetal PCA compromise. The purpose of this study was to assess the feasibility and results of endovascular treatment for these lesions. We retrospectively reviewed our experience and results of endovascular treatments for a series of nine consecutive patients with PcomA aneurysms occurring at the origin of fetal PCAs at the Department of Neurosurgery of Southwest Hospital, Chongqing, China, between June 2011 and June 2014. Depending on the angiographic findings, location and shape of the aneurysms, various therapeutic strategies were used including coiling by single or double microcatheter, balloon remodeling technique, and single or Y-stenting technique. Overall, fetal PCA was preserved patent in all cases, and complete or near complete occlusion was achieved in 8/9 cases. There was no procedure-related morbidity or mortality. With the exception of one patient who died of pneumonia 6 weeks after treatment, no clinical evidence of neurologic deterioration and hemorrhagic complication was seen during the follow-up period in the remaining 8 patients. Our experience suggests that endovascular treatment is relatively safe and technically feasible in most patients with PcomA aneurysms in the presence of fetal PCA using multiple strategies.